Case report: Significance of the large rhomboid lip in microvascular decompression: insights from two clinical cases - Ding, Feiyu; Li, Pan; Zuo, Xiaozhou; Song, Wenxiong; Xiao, Yong; Wang, Dong; Geng, Liangyuan; Hu, Xinhua; Yang, Kun; Liu, Yong; Zou, Yuanjie (Frontiers in Neurology, 2024)
The rhomboid lip (RL) is a layer of neural tissue that extends outside the fourth ventricle and is connected to the lateral recess of the fourth ventricle. Although this anatomical structure has been rigorously studied, it is often overlooked in microvascular decompression (MVD) surgery. In this report, we present two cases, one of hemifacial spasm (HFS) and one of glossopharyngeal neuralgia (GPN), in which a large RL was observed during surgery. We found that a large RL is easily confused with arachnoid cysts, and accurate identification and dissection are important to protect the lower cranial nerves.